2021
DOI: 10.1021/acs.est.1c00975
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Model Comparison of Transcriptomic Dose–Response of Short-Chain Chlorinated Paraffins

Abstract: Short-chain chlorinated paraffins (SCCPs) have attracted attention because of their toxicological potential in humans and wildlife at environmentally relevant doses. However, limited information is available regarding mechanistic differences across species in terms of the biological pathways that are impacted by SCCP exposure. Here, a concentration-dependent reduced human transcriptome (RHT) approach was conducted to evaluate 15 SCCPs in HepG2 cells and compared with our previous results using a reduced zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…In particular, the significant age-dependent accumulation tendency of SCCPs in male moose is perhaps of high concern. Recent studies revealed oxidative stress effects of SCCPs, and SCCPs showed activation of NRF2 with cross-model comparison of transcriptomic dose–response . These indicate possible testicular dysfunction induced by SCCPs via, e.g., Nrf2-mediated oxidative stress …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, the significant age-dependent accumulation tendency of SCCPs in male moose is perhaps of high concern. Recent studies revealed oxidative stress effects of SCCPs, and SCCPs showed activation of NRF2 with cross-model comparison of transcriptomic dose–response . These indicate possible testicular dysfunction induced by SCCPs via, e.g., Nrf2-mediated oxidative stress …”
Section: Resultsmentioning
confidence: 84%
“…Recent studies revealed oxidative stress effects of SCCPs, 17 and SCCPs showed activation of NRF2 with cross-model comparison of transcriptomic dose−response. 41 These indicate possible testicular dysfunction induced by SCCPs via, e.g., Nrf2-mediated oxidative stress. 42 The age-dependent accumulation potential of CPs does not necessarily mean that adult male moose are currently in danger, especially since CP concentrations were within no observed effect levels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The procedures of AOP network analysis of CRISPR screen hits were performed according to previous studies. 31 The log fold change (Log FC) of a gene was the Log FC of the sgRNA with the second largest absolute Log FC (read counts of the sgRNA in treatment vs control). Log FC of a Gene Ontology (GO) was the sum Log FC of the matched genes with the top three largest absolute Log FCs.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Specifically, a CRISPR screen in human pulmonary alveolar epithelial cells (A549 cells) was combined with molecular epidemiology analysis to identify the primary genetic factors that were involved in the vulnerability of A549 cells to adverse respiratory effects of FA. Adverse outcome pathway (AOP) network analysis of CRISPR screen hits provided mechanistic links between the primary genetic factors (molecular events) and FA-induced adverse health outcomes. , Subsequently, systematic toxicological tests (in vitro cellular tests of cytotoxicity, inflammation and fibrotic effects, and epigenetic regulation; mice lung functional and pathological tests) were performed to provide a mechanistic understanding of the primary genetic factors required to facilitate susceptibility to FA-induced lung injury. Finally, the present study also provided specific genetic risk factors for COPD as potential biomarkers for individual susceptibility to lung injury caused by exposure to FA.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate hormone levels are essential for developmental, reproductive, and metabolic functions in humans. , Thus, the subtle change in hormone levels in zebrafish is a sensitive end point that demonstrates the potential relationship between exposure to environmental toxicants and endocrine disruption. Recently, a concentration-dependent reduced zebrafish transcriptome (RZT) approach has been developed. It can characterize and quantify biological pathways potentially perturbed by substances by identifying potentially sensitive pathways, and the potency values assessed on the basis of the transcriptional point of departure (POD) can provide critical information on the bioactivity of the chemicals. , Meanwhile, an adverse outcome pathway (AOP) can condense the multilevel toxicological information on the molecular initiating events (MIEs), key events (KEs), and adverse outcomes (AOs) observed in zebrafish following chemical exposure . Several studies have attempted to use AOP for chemical risk assessment, such as hepatotoxicity, androgen/estrogen disruption, and prenatal developmental toxicity .…”
Section: Introductionmentioning
confidence: 99%